FAKTOR FAKTOR YANG MEMPENGARUHI KEJADIAN KEHAMILAN TIDAK DIINGINKAN PADA REMAJA - Ismarwati, Ismarwati; Utami, Istri (JHeS (Journal of Health Studies), 2017)
Abstract: The objective of this study was to determine the factors influencing the incidence of unwanted pregnancy in adolescents in Puskesmas Pakem that occurred in 2014-2016. The research method used descriptive qualitative with case study approach. The data collection technique was in-depth interview. The data were analyzed using Open Code. The results show that the influencing factors of unwanted pregnancy incidence in adolescents are the low knowledge of reproductive health, social permissiveness, easy access to pornographic media, the influence of close friends in the association and the parents’ parenting that tend to apply Permissive-indifferent.Keywords: unwanted pregnancy, adolescents, open code